Student perceptions of creativity and information literacy following project-based learning in Indonesian language instruction - Kamelia Marsanda Muslim; Putri Awalia Syahra; Aliem Bahri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The issue of low levels of creativity and information literacy among elementary school students necessitates an innovative, contextual learning approach. This study aims to describe the level of students’ creativity and information literacy following the implementation of a Project-Based Learning (PjBL) in third-grade Indonesian language instruction at SD Negeri Pao-Pao, Makassar. Employing a descriptive quantitative method, 24 students were selected through purposive sampling. Data were collected using a four-point Likert scale questionnaire designed to assess creativity (fluency, flexibility, originality, elaboration) and information literacy (ability to identify, evaluate, and apply information). Data analysis was conducted using SPSS version 25, including tests of validity and reliability and descriptive statistics. All instruments were found to be valid and reliable, with Cronbach's Alpha values exceeding 0.883. The mean creativity score was 82.04, and the mean information literacy score was 82.06, on a 0-100 scale, indicating that both fell within the